PERSENTASE PENETASAN TELUR IKAN BETOK (Anabas testudineus) DENGAN SUHU INKUBASI YANG BERBEDA - Dwi Aprilianti Putri; Muslim .; Mirna Fitrani (Universitas Sriwijaya, 2013)
The aims of this study was to know the effect of different temperatures on the percentage of climbing perch eggs hatching. This study has been done from October 2012 to November 2012 at Fish Breeding Unit â€œBatanghari Sembilanâ€ Indralaya. The implementation of this study include selection of the brood, rearing of brood stock, injection ovaprim, spawning, hatching eggs, larval rearing. The resultsÂ indicate that the most rapid hatching time obtained in P4 treatment (34Â° C) with a incubation time 964 minutes. Optimal incubation temperature to produce the maximum hatching percentage was 98.66% at a temperature of 34 oC. Water quality of medium were 31-340C for temperature, pHÂ 6,7-7,6 and disolved oxygen 3,3-3,8 mg.L-1. Keywords : temperature, hatching percentage hatching time, water quality.